Improving Customer Data Quality on Pension Bank Loans in Palembang-South Sumatra - Herlina, Herlina; Muyasaroh, Muyasaroh; Hairunnisa, Hairunnisa (Universitas Diponegoro, 2024)
The bank has transferred the retirement loan application service to the cooperative as one of its subsidiaries. The phenomenon that often occurs is misinformation from cooperative officers when explaining the number of credit applications that should be made. The purpose of this research is to find the right pattern and form for applying the latest data technology so that it can provide the right information in the credit application process. Measurement and analysis of research data are qualitative, with a descriptive explanation level. Viewed by place and classified as field research. Types and research strategies, including Case Studies. Retrieval, collection, and analysis techniques were carried out repeatedly and simultaneously until the data was saturated and credible. The research yields findings about internal customer data connection patterns that are accurate and up-to-date. The form of credit data management by providing recommendations and internal references to customer performance, so that process and procedure connectivity is guaranteed between Bank Financial Institutions (LKB) and Non-Bank Financial Institutions (LKBB). The conclusion from the research is that the track records or data records of retired customers at the bank must be properly and up-to-date so that when applying for the same credit at a subsidiary of the institution, there is no misunderstanding of information and guaranteed correct and correct data.